Characterization of chickpea (Cicer arietinum L.) accessions using molecular techniques - Hamdaoui, Fatiha, author; Hughes, Harrison G., advisor; Johnson, Duane, committee member; Nabors, Murray, committee member; Towill, Leigh E., committee member (Colorado State University. Libraries, 1998)
The productivity of chickpea has not been markedly improved through conventional breeding. The main problem for increasing yield is the susceptibility of the plant to the disease caused by the ascomycete Ascochyta rabiei. Because genetic markers may speed up chickpea breeding for resistance to ascochyta blight, isozymes and RAPD techniques have been applied to 56 chickpea germplasm lines which have been screened against ascochyta blight in the field and at the greenhouse in Morocco. Artificial inoculation at three locations, resulted in none of the lines evaluated being immune, seven entries were resistant and the remaining were tolerant or susceptible under Morocco conditions. Two hundred primers for RAPD assay and 15 enzymatic systems were assayed. The fifteen enzymatic systems tested were almost monomorphic and were not able to discriminate among the tested lines. Among the 200 primers tested only 6 primers yielded polymorphism. Forty- one amplification products were produced and among them four were associated with disease resistance to ascochyta blight. RAPD procedure with polyacrylamide gels differentiated among the resistant and susceptible cultivars and produced more polymorphisms than RAPD using agarose gels.
Covers not scanned.
Keywords: Chickpea